1989
DOI: 10.2135/cropsci1989.0011183x002900060037x
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod and Light Quality Effects on Cowpea Floral Development at High Temperatures

Abstract: High temperatures in tropical and subtropical zones often have detrimental effects on plants. Plants in these zones experience differences in daylength that could influence sensitivity to heat. Contrasting genotypes of cowpea, Vigna unguiculata (L.) Walp., were grown under fluorescent plus incandescent (F) or metal halide plus incandescent (MH) lamps at different daylengths (11, 12, 13, 14, or 16 h) to determine whether the sensitivity of floral development to high night temperatures is influenced by light qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Mutters and Hall [81] demonstrated that there is a distinct period during the 24-h cycle when pollen development in cowpeas is sensitive to high night temperatures. The damaging effect of high night temperature on pod set was greater in long days than in short days, and red and far-red light treatments indicated that it is a phytochrome-mediated response [82]. Although it is well established that high temperatures adversely affect grain yield in chickpea, a comparison of the effects of high day temperatures and high night temperatures is yet to be made.…”
Section: Physiological Mechanisms Underlying Heat Tolerancementioning
confidence: 99%
“…Mutters and Hall [81] demonstrated that there is a distinct period during the 24-h cycle when pollen development in cowpeas is sensitive to high night temperatures. The damaging effect of high night temperature on pod set was greater in long days than in short days, and red and far-red light treatments indicated that it is a phytochrome-mediated response [82]. Although it is well established that high temperatures adversely affect grain yield in chickpea, a comparison of the effects of high day temperatures and high night temperatures is yet to be made.…”
Section: Physiological Mechanisms Underlying Heat Tolerancementioning
confidence: 99%
“…Also note that sunlight has a low R/FR ratio of 1.2 above the canopy and an even lower ratio within dense canopies. The suppression of floral bud development under long days with high night temperatures appears to be a phytochrome-mediated photoperiod effect except that a night-break of red light during a long night did not result in floral bud suppression (Mutters et al 1989a). Suppression of floral buds under long days occurred under hot nights but was greater under the combination of hot nights and very hot days (Dow El-Madina and ).…”
Section: Heat Stress Effects In Subtropical Zonesmentioning
confidence: 98%
“…Sensitivity of pod-set to heat is greater under long days than short days, and the responses to red light during long nights, far-red light after long days, and far-red then red light after long days indicate that this is a phytochromemediated photoperiod effect (Mutters et al 1989a). Phytochrome-mediated events have a degree of circadian control, and Mutters and Hall (1992) hypothesized that there is a physiological process in pollen development that is under circadian control and only occurs during the late night.…”
Section: Heat Stress Effects In Subtropical Zonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of HNT has been widely studied in cowpea where high temperature can negatively impact fl oral bud development, fl ower development, pod set, grain fi lling, and even grain quality with the sensitive stage occurring at about 9-7 days before anthesis (Ahmed et al 1992 ;Warrag and Hall 1984 ). This stage occurs after meiosis and coincides with the release of pollen microspores from the tetrads, and high night temperature at this stage causes premature degeneration of the tapetal layer that provides nutrients to developing pollen, resulting in infertile pollen, and also adversely affects anther dehiscence in cowpea genotypes (Mutters et al 1989 ). Subjecting cowpea shoot to moderately high night temperature can also damage pod set (Warrag and Hall 1984 ); however, much hotter day temperatures did not.…”
Section: Impact Of Risingmentioning
confidence: 99%